Demographic Transition in Ethiopia: Evidence of Change from 1990 to 2016 - Minale, Amare Sewnet (Ethiopian Journal of Social Sciences, 2021)
Since the 1990s, Ethiopia has been experiencing demographic transition. The changes were the result of the country’s effort in reducing fertility and mortality rates through implementing socio-economic development programs. The demographic dividend is the economic benefit that results from improved reproductive health, a decline in fertility, and a subsequent shift in population age structure. This study explored the demographic transition and demographic dividend conditions from 1990 to 1916 in Ethiopia. In this research, secondary data from different sources such as research findings, policy documents, development plan and program reports, and analyses of censuses and surveys data were used to evaluate the demographic changes and demographic dividends. Ethiopia’s focus on children, maternal health and family planning has brought impressive results. Modern contraceptive use among women of 15-49 years old rose from 4 percent in 1990 to 35 percent in 2016.These changes have led to a total fertility decline from 7.7 children in 1990 to 4.6 children in 2016. Life expectancy at birth rose from 46 years old in 1990 to 63 years in 2016. A range of legal, policy and institutional frameworks have been developed and implemented on gender equity, equality, girls’ education, reproductive health issues and the empowerment of women. Hence, further efforts have to be made to reduce the population growth rate and total fertility and to improve the living conditions of the society. This study revealed the nature of population change in Ethiopia and future actions that need to be taken to harmonize the change in economic development and population change.